Pengaruh Belanja Modal, Pendapatan Asli Daerah, dan Dana Perimbagan Terhadap Kinerja Keuangan - Novita Sari; Benny Rojeston Marnaek Nainggolan; Rosma Ariyanti Purba; Taruli Br Saragih; Wahy Banjarnahor (COSTING : Journal of Economic, Business and Accounting, 2020)
The target of this inspection is to investigate the impact of Regional Capital Expenditures and Original Revenues and Balancing Funds on Financial Performance in North Sumatra Province. The technique used in this examination is by obtaining saturated sampling. This examination uses as many samples of 33 districts/cities was used and data were analyzed using the annual financial report (Annual Report) in North Sumatra for the period 2014-2017, which was found through the website www.bps.go.id. This examination wears a model the method of Multiple Linear Regression. Test classic assumptions and hypotheses using the F test and T-test with the SPSS program. The results show capital expenditure, original regional income, and balanced funds that were relevant to financial performance in North Sumatra Province in 2014-2017. Partially, Capital Expenditures and Regional Original Revenue has a relevant impact on Financial Performance. While the Balancing Fund has no significant impact on Financial Performance in North Sumatra Province in 2014-2017. Keywords: Capital Expenditures, Local Own Revenues, Balance Funds, Financial Performance.